Microstructure and Mechanical Properties of Microwave Sintered ZrO2 Bioceramics with TiO2 Addition - Hsien-Nan Kuo; Jyh-Horng Chou; Tung-Kuan Liu (Applied Bionics and Biomechanics)
The microwave sintered zirconia ceramics with 0, 1, 3, and 5 wt% TiO2 addition at a low sintering temperature of 1300°C and a short holding time of 1 hour were investigated. Effect of contents of TiO2 addition on microstructure and mechanical properties of microwave sintered zirconia bioceramics was reported. In the sintered samples, the main phase is monoclinic zirconia (m-ZrO2) phase and minor phase is tetragonal zirconia (t-ZrO2) phase. The grain sizes increased with increasing the TiO2 contents under the sintering temperature of 1300°C. Although the TiO2 phase was not detected in the XRD pattern, Ti and O elements were detected in the EDS analysis. The presence of TiO2 effectively improved grain growth of the ZrO2 ceramics. The Vickers hardness was in the range of 125 to 300 Hv and increased with the increase of TiO2 contents. Sintering temperature dependence on the Vickers hardness was also investigated from 1150°C to 1300°C, showing the increase of Vickers hardness with the increase of the sintering temperature as well as TiO2 addition.